Utilizing Digital Resources and Platforms to Enhance the Teaching of Arabic Language and Literature in Islamic Education - Ibrahim, Umar; Attahiru, Abubakar; Muktar, Atika; Umar Bunza, Kabiru (MultiTech Publisher, 2024)
This study explores the transformative potential of integrating digital resources and platforms to enhance the teaching of Arabic language and literature in Islamic education. Recognizing the evolving landscape of education and the growing influence of technology, this study investigates the theoretical framework supporting the use of digital tools in pedagogy within Islamic settings. A comprehensive review of literature reveals the current state of technology integration in Arabic language and literature education and identifies gaps in research that necessitate further exploration. The paper provides an in-depth examination of available digital resources and platforms suitable for language and literature instruction, categorizing them based on their applicability. Practical implementation strategies are proposed, considering the cultural and religious nuances inherent in Islamic education. The paper concludes with recommendations for future research and underscores the importance of continued exploration of emerging technologies to advance Arabic language and literature education in Islamic contexts.